Global poverty and the new bottom billion: What if three-quarters of the world's poor live in middle-income countries? - Andy Sumner (International Policy Centre for Inclusive Growth (IPC-IG), 2010)
This paper argues that the problem of global poverty has changed because most of the world's poor no longer live in poor countries, meaning low-income countries (LICs). In the past, poverty was viewed predominantly as a LIC issue. Nowadays such simplistic assumptions/classifications can be misleading because a number of the large countries that have graduated into the middle-income (MIC) category still have large numbers of poor people. We estimate that in 1990 some 93 per cent of the world's poor people lived in LICs. In contrast, we estimate that in 2007-2008 some three-quarters of the world's approximately 1.3 billion poor people now live in MICs; only about a quarter of the poor (about 370 million) live in the remaining 39 LICs, which are mostly in sub-Saharan Africa. This is a startling change over two decades. It implies there is a new `bottom billion' who do not live in fragile and conflict-affected states (FCAS) but largely in stable MICs. Further, such global patterns are evident across monetary, nutritional and multidimensional poverty measures. In reaching that conclusion, this paper discusses the origin and current definitions of the low/middle/upper-income classification; relates these classifications to International Development Association (IDA) eligibility/allocation thresholds; summarises the definition of FCAS; makes preliminary estimates for 2007-2008 and the number of poor people in each income and fragility category; makes an approximate estimation of the changes in these numbers over the last 20 years; and compares the global distribution of the poor by measures of monetary, educational, nutritional and multidimensional poverty. We recognise that the endeavour of this paper is an inherently imprecise exercise, but we argue that the general pattern is robust enough to warrant further investigation and discussion. Indeed, the results raise all sorts of questions about the definitions of country categories in themselves. They also raise numerous questions about the future of poverty reduction in heterogeneous contexts, about the role of inequality, about structural societal change, and about aid and development policy. One way of reading the data is that poverty is increasingly turning from an international to a national distribution problem, and that governance and domestic taxation and redistribution policies are becoming more important than official development assistance (ODA).
Keywords: 330